A survey of the use of oestrogens during pregnancy in the United Kingdom and of the genito-urinary cancer mortality and incidence rates in young people in England and Wales. - Kinlen, L; Badaracco, M; Moffett, J; Vessey, M (1974)
Evidence for an association between oestrogen therapy during pregnancy and adenocarcinoma of the genital tract in female offspring has come mainly from the United States where such therapy appears to have been popular. To try to obtain some estimate of the frequency of this practice in the United Kingdom, a postal questionnaire was sent in early 1973 to all Fellows of the Royal College of Obstetricians and Gynaecologists who were resident in this country at that time. A response rate of 83 per cent was obtained. From the information provided, it was estimated that about 7,500 women were treated with stilboestrol during pregnancy in the interval 1940 to 1971, mostly during the 1950s. Other oestrogens or unspecified oestrogens were given to approximately a further 4,500 patients, mainly during the 1960s. In addition, genito-urinary cancer mortality and incidence rates in young people in England and Wales were examined to try to detect any increases which might be attributable to the administration of oestrogens to pregnant women. Among females, a rise in the incidence of cancer of the cervix was noted, and among males, a rise in both the incidence of and mortality from cancer of the testis. However, there is little reason to suspect a connection between these trends and the use of oestrogens. It should also be noted that no case of adenocarcinoma of the vagina or cervix occurring in a young woman exposed to oestrogens in utero has yet been reported in the United Kingdom. However, the present study indicates that the number of women so exposed is considerable; it is, therefore, possible that such tumours will begin to appear within the next few years. © 1974.